The relationship between stress, emotional eating, and nutritional status in adolescents - Mardiyah, Sarah; Wandini, Kartika; Dwiyana, Parlin (Alma Ata University Press, 2024)
ABSTRACTBackground: The prevalence of overnutrition among adolescents in Indonesia has significantly increased from 7.3% in 2013 to 13.5% in 2018. Overnutrition at this age can increase the risk of obesity and other degenerative diseases in adulthood. Stress and eating behavior are two factors that might impact nutritional status in adolescents. Stress can trigger unhealthy eating behaviors, such as increased consumption of fast food, sugary foods and drinks, or even loss of appetite. Stress can also lead to emotional eating behavior, which is the urge to eat as a coping method when facing stress or negative pressure, and has been link to a higher BMI.Objectives: This study aims to identify the relationship between stress, emotional eating, and the nutritional status of high school students at SMA 2 Cileungsi Bogor Regency.Methods: This research is a quantitative study with a cross-sectional approach. Data collection was conducted in September 2023 at SMA 2 Cileungsi Bogor Regency. Data were collected using research instruments, including the Adolescent Stress Questionnaire – Shortened Version (ASQ-S) to determine stress data, the Dutch Eating Behavior Questionnaire (DEBQ) to determine emotional eating data, anthropometric measurements to determine the nutritional status of the respondents, and the Food Frequency Questionnaire (FFQ) to assess the frequency of respondents' consumption of various foods. This study involved 262 respondents obtained using Cluster Random Sampling technique. Results: The results showed that most of respondents in this study had normal nutritional status, accounting for 66.0%, while 8.4% were undernourished and 25.6% were overnourished. Respondents categorized as stressed were 51.9%, while the remaining 48.1% were adaptive. It was found that 54.6% of respondents fell in to the category of emotional eating, while 45.4% did not exhibit emotional eating behaviour. Based on bivariate analysis, a significant relationship was found between stress and nutritional status (p-value=0.013). There was no significant relationship between emotional eating and nutritional status (p-value=0.647).Conclusions: Stress has been shown to be significantly associated with nutritional status. KEYWORD: Nutritional status; stress; emotional eating; adolescents